Faktor Penghambat Studi Mahasiswa yang Tidak Lulus Tepat Waktu di Jurusan Pendidikan Teknik Mesin FT UNY - Widarto Widarto (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
The study aimed to identify the students who cannot finish their course on time, addressing the inhibiting factor for their course completion, identify the students' efforts and struggle on their course completion, and to understand their expectations from the school administration to accommodate their course completion. The research used survey methods with questionnaire as the instrument. The subjects of the research are the diploma and bachelor degree students of Mechanical Engineering Education Department. Data were analyzed using quantitative-descriptive technique. The results show that the inhibiting factors are the long commute to campus for supervisions, many students still taking coursework, students already have a job, passive supervisors, unconducive environment, and supervisions that were not intensively done. The students were still committed to complete their course, albeit those inhibiting factors. Students' commitments were supported by various efforts, namely intensive supervision, independent study or discussion, and finding a conducive environment to work on their final projects and theses. Students' expectations for the success of their course are the availability of final project and thesis in an earlier stage of their study, supervisor should be appointed based on their competency, increasing the allocated time of the final project schedule, the administration needs to renew the workshop's machinery and equipment, and cut off the unnecessary final project and Thesis administration steps, to make it easier for students in completing their course. Tujuan penelitian adalah untuk mengidentifikasi mahasiswa yang tidak dapat menyelesaikan studinya tepat waktu, mengetahui faktor penghambat, mengetahui usaha-usaha yang sudah dilakukan mahasiswa, dan mengetahui harapan mahasiswa kepada pengelola Jurusan Pendidikan Teknik Mesin FT UNY. Penelitian menggunakan metode survey menggunakan angket dengan analisis deskriptif kuantitatif. Objek penelitian yaitu mahasiswa D3 Teknik Mesin dan S1 Pendidikan Teknik Mesin. Hasil penelitian menunjukkan terdapat beberapa kendala penyelesaian studi yaitu: jarak yang jauh ke kampus untuk bimbingan, masih ada yang kuliah teori/praktik, sudah ada yang bekerja, dosen kurang aktif membimbing, lingkungan tempat tinggal kurang kondusif, dan bimbingan tidak intensif. Namun demikian, mahasiswa masih berkomitmen untuk menyelesaikan studinya. Keseriusan mahasiswa tersebut didukung dengan berbagai usaha, seperti bimbingan secara intensif, belajar mandiri atau diskusi, dan mencari lingkungan yang kondusif untuk mengerjakan Proyek Akhir dan Skripsi. Selain itu, harapan mahasiswa yaitu mata kuliah Proyek Akhir dan Skripsi dapat diambil lebih awal, penentuan dosen pengampu mata kuliah relevan dengan kompetensinya, jadwal pelaksanaan Proyek Akhir perlu ditambah frekwensinya, peremajakan peralatan bengkel, dan memperpendek administrasi Proyek Akhir dan Skripsi sehingga semakin mempermudah mahasiswa menyelesaikan studinya.